Modernization of Waqf Management: A Waqf Based Eco Tourism Development System on Lombok Island - Agus Salihin (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2025)
This study examines the Modernization of Waqf Management: A Waqf-Based Eco-Tourism Development System on Lombok Island. This study is a library research study that utilizes library data on state regulations related to waqf management in Indonesia. Data collection was conducted through documentation, observation, and a sufficient number of references. The results of this study explain that the development of waqf-based eco-tourism in Lombok is an innovative solution for integrating sharia principles in preserving the environment, empowering communities, and supporting sustainable development. With the support of modern technology, management transparency, and collaboration between various parties, this system can become a relevant waqf management model in the modern era and provide long-term benefits for the community and the environment.